Economic analysis of the stand-by emergency treatment (SBET) for malaria in travellers. (30th September 2020) - Ferrara, P
Abstract: Background: Stand-by emergency treatment (SBET) is a possible approach for malaria prevention in travellers to low transmission areas (such as South-Eastern Asia [SEA]), but current evidence casts doubts on its feasibility and does not allow to decide whether this strategy is economically rational. Thus, this research aimed to appraise SBET in terms of cost-benefit/cost-effectiveness analysis from the perspective of the National Health Service (NHS). Methods: To design a specific model, SBET benefits (valued as avoided direct and indirect costs of illness) were weighted against the costs associated with SBET doses to be prescribed in order to avoid one imported case of malaria. Direct healthcare costs were obtained allocating last surveillance data for imported malaria to the charge of the corresponding diagnosis-related group category and estimating outpatient care costs. Indirect social costs were calculated in terms of lost productivity. The economic framework was adjusted for the probability of malaria transmission in SEA region and weighed on the Italian context. Results: In the model, for five malaria cases estimated to be imported from SEA to Italy in 2017, it was calculated that NHS would be charged with around € 22, 487·50. Social costs were determined at € 7, 100. Thus, the total Italian public expenditure for malaria cases in SEA travellers was of € 29, 587·50 in 2017. In contrast, 50, 000 doses were considered to be carried to avoid one malaria imported case, with a cost of € 2.5 million. Conclusions: At cost-effectiveness analysis, reimbursement strategy does not lead to a favourable gain owing to the total cost of the SBET doses to be prescribed for avoiding one malaria case. The appraisal of costs and benefits brings into question the economic validation of SBET, also calling for further strategies to be reassessed for travellers to low-risk areas. Key messages: Besides the evidence of incorrect SBET use among travellers, the appraisal of costs and benefits brings into question the economic validation of this strategy. Reimbursement for SBET seems to be not cost–effective from the perspective of National Health Services.